2023
DOI: 10.1093/hr/uhad272
|View full text |Cite
|
Sign up to set email alerts
|

A QTL of eggplant shapes the rhizosphere bacterial community, co-responsible for resistance to bacterial wilt

Chao Gong,
Zhenshuo Wang,
Zhiliang Li
et al.

Abstract: Resistant crop cultivars can recruit beneficial rhizobacteria to resist disease. However, whether this recruitment is regulated by quantitative trait loci (QTL) is unclear. The role of QTL in recruiting specific bacteria against bacterial wilt (BW) is an important question of practical significance to disease management. Here, to identify QTL controlling BW resistance, Super-BSA was performed in F2 plants derived from resistant eggplant cultivar R06112 × susceptible cultivar S55193. The QTL was narrowed down t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
(55 reference statements)
0
1
0
Order By: Relevance
“…The QTLs located at chromosome 8 and chromosome 11 are novel. Recently, Gong et al [37] identified one QTL located at the 270 kb region on chromosome 10 and developed tightly linked KASP markers that can be used for new variety breeding. Due to the influence of factors such as physiological races of the pathogen of eggplant bacterial wilt, genetic background of eggplant, inoculation method of the pathogen, evaluation method of plant status, and method of inoculating the pathogen, there are differences between different research results.…”
Section: Discussionmentioning
confidence: 99%
“…The QTLs located at chromosome 8 and chromosome 11 are novel. Recently, Gong et al [37] identified one QTL located at the 270 kb region on chromosome 10 and developed tightly linked KASP markers that can be used for new variety breeding. Due to the influence of factors such as physiological races of the pathogen of eggplant bacterial wilt, genetic background of eggplant, inoculation method of the pathogen, evaluation method of plant status, and method of inoculating the pathogen, there are differences between different research results.…”
Section: Discussionmentioning
confidence: 99%